2020
DOI: 10.1007/s11240-020-01806-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and biochemical characteristics of flax transgenic callus cultures producing PHB

Abstract: Linum usitatissimum L. is a plant used by human since ancient times. Presently flax has both industrial and nutritional significance. The programmes of restoration of flax cultivation and processing are implemented to renew the importance of this plant for agriculture and economy. Genetic engineering methods and techniques of plant tissue cultures can answer this requirement, because they give the opportunity for obtaining of new plants and novel application of them. In the present study the impact of genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This plant has been used by humans dating back to ancient times, but advancements in technology relating to transgenesis allowed the prospect of modifying flax plants and also allowed for higher biomass growth, with about a 20% yield increase in comparison to control cultures. It was also observed that the cellulose in the plant cell walls of transgenic callus was structurally different, with little organization when compared to the control callus, resulting in a lower degree of crystallinity [51]. With an increasing demand on biodegradable resources in the future, use of transgenic plants is an approach that is being further developed to obtain highly efficient bioprocesses, and is an area showing immense potential.…”
Section: Phb Synthesismentioning
confidence: 99%
“…This plant has been used by humans dating back to ancient times, but advancements in technology relating to transgenesis allowed the prospect of modifying flax plants and also allowed for higher biomass growth, with about a 20% yield increase in comparison to control cultures. It was also observed that the cellulose in the plant cell walls of transgenic callus was structurally different, with little organization when compared to the control callus, resulting in a lower degree of crystallinity [51]. With an increasing demand on biodegradable resources in the future, use of transgenic plants is an approach that is being further developed to obtain highly efficient bioprocesses, and is an area showing immense potential.…”
Section: Phb Synthesismentioning
confidence: 99%